The Concept of Elite (Thoughts of Antonio Gramsci and the Study in Islamic Studies) - Amaliyah, Efa Ida; Nurhadi, Agus (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
This study attempts to reveal the elite concept from Antonio Gramsci's thought which supports elite studies in an Islamic perspective, by using library research methods. The elite according to Gramsci is a social category that is not related to class but related to hegemony. Hegemony is a winning power that is obtained through a consensus mechanism rather than through violence or oppression of other social classes. The regime spreads hegemonic power of influence because it is supported by related infrastructure organizations, namely in which intellectual obedience is supposed to occur due to cultural and political factors. This is where elites emerge which are categorized into two according to Gramsci, namely organic elites (politicians, bureaucrats, academics) and traditional elites (subject to authorities). Elites in Islam bring consequences or impacts by showing the importance of elite positions in the orderliness of civilization, the urgency of elite cadre formation in order to strengthen faith and belief as well as faith. This is important to do because of the vital role played by the elite for the advancement of society around them. Therefore, the religious elite, the religious elite, now have an obligation to participate in realizing national unity and are responsible for maintaining national resilience in its various aspects (ideological, political, economic, and socio-cultural)